Data from: Study "Arctic fox Bylot - Argos tracking" - Berteaux, Dominique (Movebank Data Repository, 2021)
Lai S, Rodrigues CW, Gallant D, Roth JD, Berteaux D. 2021. Red foxes at their northern edge: competition with the Arctic fox and winter movements. J Mammal. doi:10.1093/jmammal/gyab164 : Rapid range expansion of boreal forest predators onto the tundra may disrupt local ecological processes, notably through competition with ecologically similar species. Red foxes (Vulpes vulpes) have expanded their range northwards throughout the Canadian Arctic, inducing competition with endemic Arctic foxes (V. lagopus). We studied competition between Arctic and red foxes, with a focus on interference competition, and winter movements of red foxes using satellite telemetry and den occupancy data from both species. We worked at Bylot Island (Nunavut) and Herschel Island (northern Yukon), two sites at the northern limit of the red fox’s range. As expected, red fox home ranges were 56% larger on average than Arctic fox home ranges. However, red foxes did not exclude arctic foxes regionally nor did they prevent them from breeding successfully in their vicinity. On Bylot Island, Arctic foxes did not spatially avoid red foxes more than their conspecifics, as evidenced by similar intra- and inter-specific home-range overlaps. On Herschel Island, the red fox pair's home range extensively overlapped the home range of their Arctic fox neighbors. While red foxes tracked on Bylot Island survived several winters without expanding or leaving their home ranges, those on Herschel Island moved onto the sea ice and died. Overall, our results demonstrate low levels of interference competition between the two species in the High Canadian Arctic. When red fox density is low, as in our study areas where land protection prevents predator subsidization by anthropogenic food sources, Arctic and red foxes may be able to co-exist with limited antagonistic interactions. Our sample sizes were limited by the naturally low density of red foxes at their northernmost edge, thus replication is needed to fully understand winter space use and intraguild interactions in this species at its northern range limit.